Effects of STEM-integrated problem-based learning on mathematical critical thinking and achievement - Liza Marlian; Rayendra Rayendra; Darmansyah Darmansyah; Fetri Yeni J (Journal of Educational and Learning Studies, 2026)
This study aims to examine the effectiveness of a STEM-integrated Problem-Based Learning approach in improving students’ mathematical critical thinking skills and cognitive learning outcomes in trigonometry. A quantitative quasi-experimental design with a pretest–posttest nonequivalent control group was employed. The sample consisted of 86 eleventh-grade students at SMAN 19 Batam, divided into an experimental group taught using STEM-integrated PBL and a control group taught conventionally. The experimental group achieved higher improvements in mathematical critical thinking skills, with an N-Gain of 43.98%, compared with 20.76% in the control group. Cognitive learning outcomes also improved more strongly in the experimental group, with an N-Gain of 51.81%, compared with 28.77% in the control group. STEM-integrated PBL is effective for enhancing students’ critical thinking and cognitive achievement.